Nonlinear vibrations of a moving rail-vehicle excited by snaking and lateral impacts of wheel sets - Klasztorny, Marian (Computer Assisted Methods in Engineering and Science, 2005)
The paper develops a theory of physically non-linear vibrations of a rail-vehicle moving on a rectilinear and non-deformable track. The vibrations are excited by snaking and lateral impacts of the wheel sets. De Pater's microspin model and a new simplified model of lateral impacts are applied. An algorithm for determining quasi-steady-state vibrations of the vehicle has been formulated and programmed in Pascal. The simulations have been performed for a Shinkansen rail-vehicle moving at service velocities 160-300 km/h.